Finance–Growth Relationship in Türkiye: Long-Run Dynamics and Causality Findings (Third Sector Social Economic Review, 2026)
This study examines the long- and short-run dynamics and causality relationships between market capitalization, foreign direct investment, inflation, unemployment, and economic growth in Türkiye over the period 1993–2024. The stationarity properties of the variables were analyzed using ADF, PP, and structural break unit root tests. Given the mixed order of integration among the variables, the ARDL bounds testing approach was employed. The long-run coefficients indicate that market capitalization and unemployment exert statistically significant negative effects on economic growth, while foreign direct investment contributes positively. The negative and significant error correction term suggests that short-run deviations adjust rapidly toward long-run equilibrium. The direction of causality was tested using the Toda–Yamamoto approach, revealing bidirectional interactions between financial indicators and economic growth. The findings indicate that financial development exhibits a nonlinear and multidimensional structure and that macroeconomic stability plays a crucial role in growth dynamics. By jointly analyzing long-run equilibrium relationships and causality mechanisms, this study provides methodological and empirical contributions to the literature.
Keywords: Economic growth; Foreign direct investments; Market capitalization; Inlation; Unemployment; ARDL; Tado Yamamato